Coagulation Status and Venous Thromboembolism Risk in African Americans: A Potential Risk Factor in COVID-19. (22nd July 2020) - Frydman, Galit H.; Boyer, Edward W.; Nazarian, Rosalynn M.; Van Cott, Elizabeth M.; Piazza, Gregory
Severe acute respiratory syndrome coronavirus 2 infection (COVID-19) is known to induce severe inflammation and activation of the coagulation system, resulting in a prothrombotic state. Although inflammatory conditions and organ-specific diseases have been shown to be strong determinants of morbidity and mortality in patients with COVID-19, it is unclear whether preexisting differences in coagulation impact the severity of COVID-19. African Americans have higher rates of COVID-19 infection and disease-related morbidity and mortality. Moreover, African Americans are known to be at a higher risk for thrombotic events due to both biological and socioeconomic factors. In this review, we explore whether differences in baseline coagulation status and medical management of coagulation play an important role in COVID-19 disease severity and contribute to racial disparity trends within COVID-19.